Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/jacs.5b03084
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl Esters Are Potent Inhibitors of Caseinolytic Protease P and Reveal a Stereogenic Switch for Deoligomerization

Abstract: Caseinolytic protease P (ClpP) represents a central bacterial degradation machinery that is involved in cell homeostasis and pathogenicity. The functional role of ClpP has been studied by genetic knockouts and through the use of beta-lactones, which remain the only specific inhibitors of ClpP discovered to date. Beta-lactones have served as chemical tools to manipulate ClpP in several organisms, however, their potency, selectivity and stability is limited. Despite detailed structural insights into the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 93 publications
(135 citation statements)
references
References 39 publications
1
120
1
14
Order By: Relevance
“…Select lactones, including E2 and phenyl esters such as AV170 , are known to destabilize tetradecameric ClpP and to induce its dissociation into inactive heptamers. 10,11 In fact, deoligomerization of LmClpP2 could be observed upon E2 binding, while the tetradecameric complex was retained with both the CMKs and D3 (Fig. S4†).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Select lactones, including E2 and phenyl esters such as AV170 , are known to destabilize tetradecameric ClpP and to induce its dissociation into inactive heptamers. 10,11 In fact, deoligomerization of LmClpP2 could be observed upon E2 binding, while the tetradecameric complex was retained with both the CMKs and D3 (Fig. S4†).…”
Section: Resultsmentioning
confidence: 96%
“…These studies suggested that steric clash of the inhibitor within the active site triad triggers a rearrangement at the heptamer interface, causing dissociation of the ClpP tetradecamer into two heptameric rings. 11 Recently, the first reversible ClpP inhibitors were reported, which distort the active site catalytic triad through structural rearrangements. 12 However, this inactive state of the ClpP peptidase could be reversed through formation of the ClpXP complex, highlighting the power of conformational control within this dynamic system.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the roles that bacterial Clp proteins play in cell division, stress response and pathogenicity (Frees et al, 2014), have placed them at the center of several drug discovery programs (Böttcher and Sieber, 2008; Brötz-Oesterhelt and Sass, 2014; Conlon et al, 2013; Gersch et al, 2015; Hackl et al, 2015). Our data demonstrate that targeting the P. falciparum plastid-localized Clp proteins is a viable strategy for antimalarial drug development and future work will allow us to repurpose highly active antibacterial compounds as effective anti-malarial agents.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Sieber and colleagues 49 has discovered a new class of potent ClpP inhibitors, the phenyl esters (AV170; Figure 3a). Discovered using an unbiased screen of 137 000 synthetic compounds in a fluorogenic assay for ClpP activity, phenyl esters act by the same covalent modification of Ser98 as β-lactones.…”
Section: Clpp Inhibitorsmentioning
confidence: 99%
“…Efforts to increase potency revealed a trade-off between stability and reactivity. 49 Although ClpP inhibition shows promise as a mechanism of action, further development and discovery of novel scaffolds is clearly required. Moreover, given recent evidence of drug resistance in certain clpP knockout strains, 34,36 some caution down this path may be warranted.…”
Section: Clpp Inhibitorsmentioning
confidence: 99%